Legal Aspects of Cooperation Agreements with the Right to Buy Back Shares Accompanied by a Power of Attorney to Sell Under Hand - sholikah, Dianita Imroatus; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Limited liability companies often require additional capital for business development, one solution is to enter into a cooperation agreement with investors through a share return mechanism. The cooperation agreement is made accompanied by a temporary transfer of shares to a second party, with a provision for the first party to repurchase the shares after the cooperation period ends, a practice like this is commonly found in the environment of closed limited liability companies. In this practice, it is also generally accompanied by the granting of a power of attorney to sell from the second party to the first party as a form of guarantee for the implementation of the share return. This study aims to examine the legal aspects of the cooperation agreement, assess the validity of the power of attorney to sell in transferring shares back to the original party, and analyze this practice based on the theory of legal certainty and utility. The research method used is a normative juridical method with a statutory and conceptual approach. Based on the research results, cooperation agreements containing share repurchase clauses are essentially valid under civil law as long as they meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code. However, the use of an irrevocable power of attorney to sell privately for the purpose of returning shares raises potential legal issues and opens up room for legal uncertainty in their implementation. From a utility theory perspective, this can provide efficiency and practical benefits for the parties, provided that the rights and obligations of the parties are clearly regulated and there is balanced legal protection.